Signal peptide‐CUB‐EGF domain‐containing protein 1 (SCUBE1) levels in patients with overt and subclinical hyperthyroidism: effects of treatment. (12th November 2015) - Erem, Cihangir; Civan, Nadim; Coskun, Hulya; Mentese, Ahmet; Suleyman, Akile Karacin; Altay, Diler Us; Akgul, Zeynep; Deger, Orhan
Summary: Background and Objectives: Signal peptide‐CUB‐EGF domain‐containing protein 1 (SCUBE1) has been shown to increase in parallel with platelet activation in acute ischaemic and thrombotic diseases. There has been no study evaluating SCUBE1 levels in patients with overt hyperthyroidism (OHyper) and subclinical hyperthyroidism (SHyper), conditions which are known to show impairment of both endothelial and platelet function. This study sought to evaluate SCUBE1 concentrations in patients with SHyper and OHyper, and assessed the effects of antithyroid drug (ATD) therapy on circulating SCUBE1 levels. Design and Methods: Forty‐five untreated patients with OHyper, 20 untreated patients with SHyper and 30 age‐ and sex‐matched healthy controls were prospectively included in the study. Biochemical and hormonal parameters were evaluated in all patients before and after treatment. Results: Compared with the control subjects, SCUBE1 levels were significantly increased in patients with SHyper and OHyper ( P < 0·0001 and P = 0·002, respectively). SCUBE1 levels were not significantly different in patients with OHyper compared with patients with SHyper. There was no significant correlation between serum thyroid hormones and SCUBE1 levels. Plasma SCUBE1 levels decreased significantly in both OHyper and SHyper after ATD treatment ( P < 0·05). Conclusions: Increased SCUBE1 levels in both SHyper and OHyper patients may reflect increased platelet activation and possible endothelial dysfunction, which might augment the risk for atherosclerotic and atherothrombotic complications. SCUBE1 may be used as a reliable marker of endothelial damage in hyperthyroidism, especially in the subclinical period.